Oxidative RNA Modifications as an Early Response of Soybean (Glycine max L.) Exposed to Copper and Lead - Chmielowska-Bąk, Jagna; Shcheglova, Ekaterina; Rosik, Konrad; Yushin, Nikita; Zinicovscaia, Inga; Deckert, Joanna (Frontiers in Plant Science, 2022)
Plant exposure to metals is associated with accumulation of reactive oxygen species, which mediate oxidation of various molecules including lipids, proteins and nucleic acids. The aim of present study is evaluation of the impact of short term Cu and Pb treatment on oxidative events in the roots of soybean seedlings, with special emphasis on RNA oxidation. The results show that increase in RNA oxidative modification, 8-hydroxyguanosine (8-OHG), constitutes very early response to both applied metals, observed already within the first hour of treatment. Exposure to Cu and Pb resulted also in increase in superoxide anion and hydrogen peroxide levels and intensified lipid peroxidation. However, this responses were most prominent after longer treatment times. On the other hand no changes were observed in the level of protein carbonylation.